The Influence of Work Ability, Work Motivation, and Employee Engagement on Employee Performance at PT. Nenggapratama Internusa - Rahman, Endi; Pata, Rizky; Isa, Ramlan Amir (one million dreams corporation, 2025)
Employee performance measurement is the company's initial effort to identify skill gaps and ensure that each individual contributes maximally to the achievement of sales targets and dealer operations. This study aims to analyze the influence of work ability, work motivation, and employee engagement on employee performance at PT. Nenggapratama Internusa, a Suzuki Car Dealer in Gorontalo. The research method is quantitative descriptive where the research data was obtained through a questionnaire with saturated sampling totaling 68 employees using a multiple linear regression analysis approach. The results of the study indicate that work ability and work motivation have a positive and significant effect on employee performance, but not for employee engagement on employee performance which was found to have a positive and insignificant effect. Companies need to encourage employee capability improvement through appropriate training and increasing their work motivation. Increasing employee engagement by means of appreciation and providing incentives based on target achievement is expected to improve employee performance